Analisis Butir Soal Ujian Tematik Siswa Kelas 5 Tema 6 Semester Ganjil T.A 2024.2025 SDN 064987 Medan - Risma Hartati (Mathematics Education Study Program, 2025)
The purpose of this study was to determine the quality of the exam questions tested on students in the odd semester of grade 5 of elementary school. This study is a qualitative study conducted in different schools with different question categories, namely thematic and subjects. The data collection in the form of exam questions and student answer keys will be examined using Microsoft Excel technology to determine the level of quality of the tests tested on students. By conducting this study, it is hoped that educators and teachers will be able to design questions with good quality so that the questions tested become questions that have the best quality and students are able to understand and answer questions according to their abilities.